The judge, the judiciary, and the court : individual, collegial and institutional judicial dynamics in Australia - Appleby, Gabrielle; Lynch, Andrew, 1973- (Cambridge : Cambridge University Press, 2021)
The Judge, the Judiciary and the Court is aimed at anyone interested in the Australian judiciary today. It examines the impact of the individual on the judicial role, while exploring the collegiate environment in which judges must operate. This professional community can provide support but may also present its own challenges within the context of a particular court's relational dynamic and culture. The judge and the judiciary form the 'court', an institution grounded in a set of constitutional values that will influence how judges and the judiciary perform their functions. This collection brings together analysis of the judicial role that highlights these unique aspects, particularly in the Australian setting. Through the lenses of judicial leadership, diversity, collegiality, dissent, style, technology, the media and popular culture, it analyses how judges work individually and as a collective to protect and promote the institutional values of the court.
The judge, the judiciary, and the court : the individual, the collective, and the institution / Gabrielle Appleby and Andrew Lynch -- Re-examining the judicial function in Australia / Joe McIntyre -- The chief justice : under relational and institutional pressure / Gabrielle Appleby and Heather Roberts -- Dismantling the diversity deficit : towards a more inclusive Australian judiciary / Brian Opeskin -- Technology and the judicial role / Monika Zalnieriute and Felicity Bell -- Emotion work as judicial work / Sharyn Roach Anleu and Kathy Mack -- The persistent pejorative : judicial activism / Tanya Josev -- Judicial collegiality / Sarah Murray -- Individual judicial style and Institutional norms / Andrew Lynch -- Values and judicial difference in the high court / Rachel Cahill-O'Callaghan -- Judges and the media / Matthew Groves -- The 'good judge' in Australian popular television culture / Penny Crofts.
Title from publisher's bibliographic system (viewed on 07 May 2021).
Keywords: Justice, Administration of -- Australia; Courts -- Australia; Judges -- Australia